Urbanization Rapidity and Its Impact on Shuklagandaki Municipality - Upadhyay, Rajeev; Paudel, Naresh; Poudel, Rabindra (Pargatishil Darpan, 2024)
This study examines the trends and causes of urbanization as well as how they affect Nepal's Shuklagandaki Municipality, which is urbanizing quickly. Using a mixed-methods approach, the study incorporates data from both qualitative and quantitative sources. Quantitative information was gathered from field survey and qualitative data were collected from public reports, census records, and government statistics to examine demographic and economic developments in the municipality during the previous 20 years. Through in-depth interviews with important stakeholders, such as public servants, company owners, and community leaders, qualitative data were acquired. Regression analysis and other descriptive and inferential statistics were used in the data analysis process. The results show that throughout the past 20 years, Shuklagandaki Municipality has had notable increase in both demographic and economic metrics. Urban expansion was primarily driven by population increase and economic development; infrastructural improvements, while significant, were secondary. The necessity for planning and policy initiatives that support sustainable growth while attending to the needs and well-being of present and future inhabitants is highlighted by the difficulties and possibilities brought about by the fast urbanization. The article finishes with a summary of the key results, a discussion of the research limitations, and references for future research topics to fill in the gaps in the body of knowledge and address unresolved issues with urban expansion in Shuklagandaki Municipality.